2016
DOI: 10.1242/bio.020958
|View full text |Cite
|
Sign up to set email alerts
|

The roles of Syx5 in Golgi morphology and Rhodopsin transport inDrosophilaphotoreceptors

Abstract: SNAREs (SNAP receptors) are the key components of protein complexes that drive membrane fusion. Here, we report the function of a SNARE, Syntaxin 5 (Syx5), in the development of photoreceptors in Drosophila. In wild-type photoreceptors, Syx5 localizes to cis-Golgi, along with cis-Golgi markers: Rab1 and GM130. We observed that Syx5-deficient photoreceptors show notable accumulation of these cis-Golgi markers accompanying drastic accumulation of vesicles between endoplasmic reticulum (ER) and Golgi cisternae. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
4
5
0
Order By: Relevance
“…However, it is also possible that TRAPPC11 allows the complex to have an additional activity that budding yeast no longer requires. Our finding that in some tissues, TRAPPIII is found on the trans-Golgi as well as the cis-Golgi provides some support for this possibility as Rab1 is widely believed to function only on the cis-Golgi ( Satoh et al, 2005 , 2016 ), and consistent with this, we could only detect YFP-Rab1 on the cis-Golgi in these tissues (Fig. S5).…”
Section: Discussionsupporting
confidence: 78%
“…However, it is also possible that TRAPPC11 allows the complex to have an additional activity that budding yeast no longer requires. Our finding that in some tissues, TRAPPIII is found on the trans-Golgi as well as the cis-Golgi provides some support for this possibility as Rab1 is widely believed to function only on the cis-Golgi ( Satoh et al, 2005 , 2016 ), and consistent with this, we could only detect YFP-Rab1 on the cis-Golgi in these tissues (Fig. S5).…”
Section: Discussionsupporting
confidence: 78%
“…The immunostaining of Na + K + ATPase at the basolateral membrane was also reduced. These phenotypes were similar to those caused by the loss of Syx5, which regulates ER-to-Golgi transport, and these findings are in agreement with those of a recent study that showed that fly TRAPPIII complex is a Rab1-GEF (Riedel et al, 2018;Satoh et al, 2016). We next investigated the influence of TRAPPIII deficiency on Rab1 and Rab11 localization.…”
Section: Trappiii But Not Trappii Is Necessary For Rh1 Transportsupporting
confidence: 89%
“…The immunostaining of Na + K + ATPase at 265 the basolateral membrane was also reduced. These phenotypes were similar to those 266 caused by the loss of Syx5, which regulates ER to Golgi transport, and these findings 267 are in agreement with those of a recent study that showed that fly TRAPPIII is a Rab1-268 GEF (Riedel et al, 2018;Satoh et al, 2016). We next investigated the influence of 269 TRAPPIII-deficiency on Rab1 and Rab11 localization.…”
Section: Pcs Is Not Necessary For Rab11 Membrane Recruitment 235supporting
confidence: 82%